Deception in high places a history of bribery in Britain's arms trade - Gilby, Nicholas (Pluto Press, 2014)
Deception in High Places' charts British government involvement in arms trade corruption and presents a history of bribery in Britain's arms deals with Saudi Arabia. It includes the backstory of the controversial termination of a Serious Fraud Office corruption investigation following pressure by the Saudi royal family and the British establishment.